2016
DOI: 10.1158/1078-0432.ccr-15-1900
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of Phosphodiesterase Type 5 in Human Breast Cancer Cell Lines and Tissues: Implications for Targeted Therapy

Abstract: Purpose: By catalyzing cGMP hydrolysis, phosphodiesterase (PDE) 5 is a critical regulator of its concentration and effects in different (patho)physiologic processes, including cancers. As PDE5 is a known druggable target, we investigated the clinical significance of its expression in breast cancer and the underlying mechanisms by which it may contribute to tumor progression.Experimental Design: PDE5 expression was evaluated in seven breast cancer cell lines by RT-PCR and immunoblotting. To examine the impact o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 48 publications
2
51
0
Order By: Relevance
“…In conclusion, due to growing evidence about the benefits of PDE5 inhibitors as anticancer drugs [51] and about PDE5 as a new potential target for breast cancer therapy [10], the results of this work can be interesting since they can offer the basis to develop a new generation of inhibitors that combine old (aromatase) and new (PDE5) targets for breast cancer therapy. …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In conclusion, due to growing evidence about the benefits of PDE5 inhibitors as anticancer drugs [51] and about PDE5 as a new potential target for breast cancer therapy [10], the results of this work can be interesting since they can offer the basis to develop a new generation of inhibitors that combine old (aromatase) and new (PDE5) targets for breast cancer therapy. …”
Section: Resultsmentioning
confidence: 96%
“…Moreover, it was demonstrated that treatment with sildenafil significantly decreases migration and invasion of MCF-7 breast cancer cell line, where PDE5 and aromatase are contemporarily overexpressed [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Fallahian et al60 concluded that increased activation of protein kinase G by cGMP induces apoptosis and growth arrest in breast cancer MCF-7 and MDA-MB-468 cells. Furthermore, the nonspecific PDE-5 inhibitor exisulind and its analogs selectively induce the apoptosis of various human prostate, colon, and breast cancer cells, and the effect that was attributed to inhibition of PDE-5 expression 7,61…”
Section: Discussionmentioning
confidence: 99%
“…PDE-5 has been shown to be overexpressed in multiple human carcinomas including breast cancers, colon adenocarcinoma, bladder squamous carcinoma, and lung cancers that have significantly lower cGMP levels than normal cells 1,3–7. This implies that selective inhibition of PDE-5 may have antineoplastic effects and may increase the specificity of a given chemotherapeutic agent.…”
Section: Introductionmentioning
confidence: 99%